Physical and perceptual-cognitive demands of top-class refereeing in association football - Helsen, W. F.; Bultynck, J. B. (Journal of Sports Sciences, 2004)
The aim of this study was to examine the physical and perceptual-cognitive demands imposed on UEFA top-class referees and assistant referees during the final round of the Euro 2000 Championship. To investigate the physical workload, the heart rates during matches were monitored by short-range radio telemetry and translated to different workloads expressed as a percentage of maximal heart rate. For measurement of the perceptual-cognitive workload, video-recordings of games were used to obtain the average number of observable decisions taken by a referee. On average, referees and assistant referees performed the matches at 85 +/- 5% and 77 +/- 7% of their maximal heart rate, respectively. Over the 31 games, the mean number of observable decisions was 137 (range 104-162), 64% of which were based on communication with the assistant referees and/or the fourth official. To optimize the physical preparation of top-class match officials, the results of this study support the application of intensive and intermittent training sessions, which should place priority on high-intensity aerobic stimuli. In addition, video training is discussed as an additional method for improving match officials' decision making.